2020
DOI: 10.1177/1753193420958553
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index and the risk of development of Dupuytren’s disease: a Mendelian randomization study

Abstract: We performed Mendelian randomization analyses of body mass index and waist–hip ratio adjusted for body mass index in Dupuytren’s disease using summary statistics from genome-wide association study meta-analyses. We found that adiposity is causally protective against Dupuytren’s disease, with the inverse-variance weighted Mendelian randomization analysis estimating that a 1 standard deviation increase in body mass index (equivalent to 4.8 kg/m2) leads to 28% (95% confidence interval: 18–37%) lower relative odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…All studies indicated Mendelian randomization in the title and/or abstract, provided a rationale for the study and the objective, and provided information on the data sources used. In two studies, information on the number of cases and non-cases for the disease outcome(s) was not found [ 25 , 29 , 30 ]. Most studies obtained genetic instruments for BMI from a genome-wide association study based on the Genetic Investigation of ANthropometric Traits consortium with or without UK Biobank [ 58 , 60 , 61 ] and used 14 to several hundred SNPs as instrumental variables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies indicated Mendelian randomization in the title and/or abstract, provided a rationale for the study and the objective, and provided information on the data sources used. In two studies, information on the number of cases and non-cases for the disease outcome(s) was not found [ 25 , 29 , 30 ]. Most studies obtained genetic instruments for BMI from a genome-wide association study based on the Genetic Investigation of ANthropometric Traits consortium with or without UK Biobank [ 58 , 60 , 61 ] and used 14 to several hundred SNPs as instrumental variables.…”
Section: Resultsmentioning
confidence: 99%
“…The number of MR studies based on independent study samples for each disease category was two for diabetes mellitus [ 7 , 8 ], 13 for circulatory system diseases [ 9 – 21 ], three for respiratory diseases [ 8 , 22 , 23 ], six for digestive system diseases [ 24 29 ], five for musculoskeletal system diseases [ 30 34 ] plus FinnGen consortium (for osteoporosis), five for nervous system diseases [ 35 39 ], and 14 for neoplasms [ 40 – 53 ]. Among the selected studies, six studies included East-Asian (Chinese [ 11 , 25 , 42 ] and Japanese [ 48 , 50 ]) or Chilean [ 53 ] individuals, whereas the remaining studies included individuals of European ancestry or mixed (trans-ancestry) populations.…”
Section: Resultsmentioning
confidence: 99%
“…The epidemiological literature on circulating lipids, apolipoproteins and risk of DD is scarce, and the most cited papers date back to the 1980's and 1990's 14,15 . In recent years, however, an inverse association between a high BMI and the risk of DD have been reported in several studies 11,12,31 , indicating a possible protective factor linked to the fat tissue. The putative biological mechanisms behind this associations is not known but lower serum testosterone among obese individuals has been proposed as one hormonal factor of importance, possibly decreasing the risk for DD 31 .…”
Section: Bmi and Apolipoproteinsmentioning
confidence: 99%
“…In recent years, however, an inverse association between a high BMI and the risk of DD have been reported in several studies 11,12,31 , indicating a possible protective factor linked to the fat tissue. The putative biological mechanisms behind this associations is not known but lower serum testosterone among obese individuals has been proposed as one hormonal factor of importance, possibly decreasing the risk for DD 31 . In our study, we found a similar pattern of associations; men with incident DD during follow-up had a lower mean BMI at baseline compared to men without DD.…”
Section: Bmi and Apolipoproteinsmentioning
confidence: 99%
“…The association between obesity and Dupuytren's disease (DD) is highly biologically unusual, being one of only two diseases where obesity is found to be protective in the development of the disease (Majeed et al, 2021). Large epidemiological cohort studies have suggested that obesity is protective for DD (Gudmundsson et al, 2000;Hacquebord et al, 2017;Kuo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%